-6(2t+6)=-12

Simple and best practice solution for -6(2t+6)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2t+6)=-12 equation:


Simplifying
-6(2t + 6) = -12

Reorder the terms:
-6(6 + 2t) = -12
(6 * -6 + 2t * -6) = -12
(-36 + -12t) = -12

Solving
-36 + -12t = -12

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + -12t = -12 + 36

Combine like terms: -36 + 36 = 0
0 + -12t = -12 + 36
-12t = -12 + 36

Combine like terms: -12 + 36 = 24
-12t = 24

Divide each side by '-12'.
t = -2

Simplifying
t = -2

See similar equations:

| 3r=-18 | | x=7y-47 | | 0.14y+0.07(y+6000)=1260 | | 12-3(4x+2)=3x+4(x-8) | | 3[x+5(6-x)+24]-11=79-15x | | 3-y=6y+7 | | 4(-18+24)= | | 2x-70=50+6x | | (-6+12i)(-7-9i)=0 | | 2x^3-3x=6x^2 | | 6r^2+12r+24=0 | | -(9-6a)-(10+5a)-14=-(2-6a)+(-a)+1 | | -5(n+4)+22=-3n-4 | | 15x-2(x+1)=154 | | 14x-4(4x-2)=5(2x+1)+3 | | 20.00-1.45*v=1.15 | | -9x-156=42-2x | | 14x-3(x+1)=96 | | 53=-16t^2+75t+30 | | 11x+9=4x+5 | | 4x^3+5x=13x^2 | | -[3x-(2x+6)]=-1-[3(2x-4)-3x] | | 8.12x+0.32=3.76x-3.23 | | 14x-3(x+1)=63 | | -10(s+3)=51 | | r^2+2r+4=0 | | y+6-10=0 | | 2/x+6=3/5x-11 | | 3x+3-4x=89 | | -10s+-30=51 | | 3x^3+5x^2=x | | 3.5x=y-7 |

Equations solver categories